Analysis of the Coverage of Paratriathlon and Paratriathletes in Canadian Newspapers - Gregor Wolbring; Brian Martin (Sports, 2018)
From recreational to elite levels, sport has many benefits for disabled people. At the same time, it is acknowledged that there is a trickle-down problem from para-elite sport to sport participation of disabled people, in general. Newspapers are one form of media that sets agendas and influences public opinion. Many studies have highlighted problematic aspects of parasport and para-athlete coverage in newspapers. Paratriathlon was one of two new events added to the Paralympics in Rio 2016, which increased its visibility in the public domain. We investigated the coverage of paratriathlon and paratriathletes in 300 Canadian newspapers using the ProQuest database Canadian Newsstream as a source, and utilizing a descriptive quantitative and a qualitative thematic content analysis. The main themes evident in the reporting on paratriathlon and paratriathletes, in the three hundred Canadian newspapers we covered, were the supercrip imagery of the para-athlete, personal stories mostly linked to the supercrip imagery, and the theme of able-bodied athletes in juxtaposition to the para-athletes. Using the lens of the four legacy goals of the International Paralympic Committee, we conclude that our findings are detrimental to the fulfillment of the four legacy goals.